Modelagem de conectividade entre áreas protegidas: proposta de rede de corredores para gestão integrada da paisagem na Região Hidrográfica Sul Catarinense - Mourão, Carla (Universidade Federal de São Carlos, 2023)
Anthropic pressures are fragmenting the landscape and condemning global biodiversity, which performs numerous ecological functions and provides ecosystem services for the maintenance and well-being of humanity on Earth. To ensure the preservation of these services, we need to mitigate the fragmentation process and thus achieve its full cascade effect. One of the main solutions for this process is to establish connections between the remnants of vegetation which allow the flow of species and thus maintain the genetic variation of populations. The objective of this study was to model a connectivity network between the Protected Areas in the Southern Hydrographic Region of Santa Catarina – Brazil. The proposed Biodiversity Corridors are more than areas of physical connection of habitats, but also a landscape planning unit in which the interstice zones are sustainable with respect to the use of land and natural resources, preserving biodiversity. Structural factors were considered based on maps of land use and land cover, size of forest remnants, Permanent Preservation Areas, terrain slope and as a differential, an ecological factor was inserted, the key species richness to provide a functional connectivity network based on the analysis of the lowest cost path for the formation of each corridor corresponding to the connection of the indicated points. As a result, the pixels that contained the lowest values resulting from the combination of cumulative origin and destination costs were identified, and nine potential corridors were modeled. In the analyzes of the corridors, it was possible to verify their respective uses and land cover and the conflict that exists with the legally protected areas, in addition to analyzing the vegetation index of each route and detecting the bottlenecks that were formed, in this way, determining the areas priorities for conservationist actions and propose guidelines for the integrated management of the landscape in the pursuit of quality of life.
Connectivity modeling between protected areas: proposal for a network of corridors for integrated landscape management in the Southern Santa Catarina Hydrographic Region
Keywords: Conservação da biodiversidade; Rede de conectividade; Planejamento sustentável; Biodiversity conservation; Connectivity network; Sustainable planning; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOFISICA::SENSORIAMENTO REMOTO; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::GEOECOLOGIA